A Small CO2 Leakage May Induce Seismicity on a Sub‐Seismic Fault in a Good‐Porosity Clastic Saline Aquifer. Issue 12 (16th June 2022) - Glubokovskikh, Stanislav; Saygin, Erdinc; Shapiro, Serge; Gurevich, Boris; Isaenkov, Roman; Lumley, David; Nakata, Rie; Drew, Julian; Pevzner, Roman
Abstract: Despite public concerns, only a few CO2 injections into saline aquifers have reported microseismicity. We analyze passive seismic monitoring of a small (15, 000 tonnes and 0.15 MPa pressure) injection of supercritical CO2 ‐rich mixture for Stage 2C of the CO2CRC Otway Project (Victoria, Australia), which induced 19 detectable events with maximum moment magnitude M W ‐0.5. The locations and dynamic parameters of the triggered events indicate a reactivation of a small fault patch where CO2 flowed through the fault. Time‐lapse seismic images of the plume and reservoir simulations show that the reactivation occurred when the CO2 plume reached this fault. This might be indicative of a fault weakening by the plume that enabled subsequent reactivation by pressure variations. Our observations suggest that a leakage from a commercial‐scale storage may trigger felt seismicity in the overburden without strong overpressure, thus, the de‐risking workflows should involve a detailed study of small faults. Plain Language Summary: Geological carbon storage is one of the key technologies for reducing the greenhouse gas effects. The storage projects may reactivate subsurface faults and lead to felt earthquakes and even surface deformations. We present a new case study, Stage 2C of the CO2CRC Otway Project (Victoria, Australia), where a small leakage‐like injection triggered seismicity that could be detected by high‐sensitivity sensors but is way below the "felt" levels. Typically, pre‐existing faults and fractures are triggered by pressure build‐up from an injection. Timing and locations of the triggered micro‐earthquakes at the Otway Project may suggest that the injected gas might have weakened the rocks filling the fault gouge thus making the fault more prone to reactivation. Our study implies that even a small leakage into such a reservoir, driven mainly by buoyancy, has seismogenic potential and thus this risk should be carefully considered by site operators for geological carbon storage projects. Key Points: A low‐pressure injection of 3, 000 tonnes of supercritical CO2 into a high‐quality sandstone aquifer induced detectable seismicity All of the seismic events are located on a small fault undetected in the seismic images prior to the injection The seismic monitoring data suggest that a fluid‐rock interaction enabled the fault's reactivation by the increased pore pressure